MAKING TEACHING AND LEARNING MORE EFFECTIVE DURING COVID-19 PANDEMIC AND BEYOND - Feliks, Tans; Nalley, Hilda M; Bhae, Yohanes (Academic Journal of Educational Sciences, 2021)
In this article, we acknowledged that it is formal teaching and learning that has contributed much in creating a great civilization as we have it in the last few centuries. Yet, we argue that teaching and learning activities in our formal schools in general, during this Covid-19 pandemic in particular, are no longer that effective as shown by such facts as students who are not active in learning, who drop out of our school system, and who fail in schools and beyond. To overcome this problem, we insist that the following concepts be implemented in schools: 1. teaching should be no longer seen as transferring knowledge, skills, and values, but it has to be viewed as facilitation of students’ learning so that they can be indepent, healthy, and socially and environmentally great; 2. learning should not also be seen as memorizing what teachers teach, but to a process of real development within students themselves so that they can be independent with great characters in and after schooling; 3. dialogical education should be the basis of our formal education; 4. students’ potentials, interests, and needs should be the focusses of our formal education barbarslot ; and, 5. educational evaluation should be more comprehensively done, that is, it should focus on students’ cognition, skills, and affection, rather than on their cognitive aspect alone. Barbarslot adalah permainan digital yang meniru mesin slot klasik yang biasa ditemukan di kasino. Permainan ini sangat populer karena mudah dimainkan, tidak memerlukan keahlian khusus, dan menawarkan peluang menang yang menggiurkan.